A Systematic Review of Indonesia’s Heritage Tourism in Perspective of Smart Tourism Conceptual Model - Absari, Dhiani; Djunaidy, Arif; Susanto, Tony Dwi (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2023)
Currently, smart tourism has been adopted by cities in many countries. But this concept has various meaning built on different point of view of the smart tourism initiatives. This paper aims to give contribution on conceptual model formulation for smart tourism in process approach, using heritage tourism as case study. A literature review using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) was carried out to achieve an understanding of the term smart tourism itself, with reference to various literature from qualified journals. From the literature review, various terms related to the definition, objectives, characteristics, inputs and outputs of smart tourism will be obtained. A semantic process with content analysis method to help determine the dominant factors/variables as important objects of Smart Tourism. The model to be built describes the components that influence the smart tourism process. This model also considers some local values that are used in general and particular in tourism policies that have been implemented in Indonesia. These values are believed to have an influence and characteristic of the smart tourism model in Indonesia. In the end, the model also describes the expected results of the smart tourism process.